SEGMENTASI DAN ANALISIS PERILAKU KONSUMEN KOPI BUBUK - Utami, Riza Wahyu (Jurnal Sosial Ekonomi Pertanian, 2009)
The purpose of this study was to know the consumer segmentation of ‘555’ Ground Coffee in Capital city of Nusa Tenggara Barat Province, to know the variables which influence the consumer behaviour from buying ‘555’ Ground Coffee and also knowing the marketing  prospect of ‘555’ Ground Coffee based on sales trend. The data were analyzed from 99 respondents in Mataram and also from secondary data series of sales over three years in recent. Chi Squared analysis, Linear Regression and least squared Trend Method was also used to analyze the data. The result of Chi Squared analysis showed that there was a differ segmentation of ‘555’ Ground Coffee consumer. The segmentation of ‘555’ Ground Coffee was divided into three segments which is: low income level, middle income level and high income level. Linear Regression Analysis found that variables of customs, education, price, income, promotion and profession were significant toward consumer buying decision. In other side, variable of quality, age and ethnic were not significantly related. Moreover, income was the highly significant variable which affect on consumer buying decision. Least square trend analysis on sales showed that ‘555’ Ground Coffee marketing have a good prospect in the future. The study suggested that company have to responds to consumer wants in order to make them become loyal, reaching more consumer and also taking more positive movements toward ‘555’ Ground Coffee future. Government is suggested to play roles by developing and promoting ‘555’ Ground Coffee in order to make them more famous, instead that it was one of their region assets. Moreover, central government is suggested to inventory the potential of each region, so that it can be used to increase country’s devisa. Keyword: Segmentation, Consumer Behaviour, Ground Coffee